Evidence for the latest fossil Pongo in southern China. Issue 170 (September 2022) - Liao, Wei; Harrison, Terry; Yao, Yanyan; Liang, Hua; Tian, Chun; Feng, Yuexing; Li, Sheng; Bae, Christopher J.; Wang, Wei
Abstract: Pongo fossils with precise absolute age brackets are rare, limiting our understanding of their taxonomy and spatiotemporal distribution in southern China during the Late Pleistocene. Twenty-four isolated teeth of fossil orangutans were recently discovered during excavations at Yicun Cave in Guangxi Zhuang Autonomous Region, southern China. Here, we dated the fossil-bearing layer using Uranium-series dating of the associated flowstone and soda straw stalactites. Our results date the Yicun orangutan fossils to between 66 ± 0.32 ka and 57 ± 0.26 ka; thus, these fossils currently represent the last appearance datum of Pongo in southern China. We further conducted a detailed morphological comparison of the Yicun fossil teeth with large samples of fossil ( n  = 2454) and extant ( n  = 441) orangutans from mainland and island Southeast Asia to determine their taxonomic position. Compared to other fossil and extant orangutan samples, the Yicun Pongo assemblage has larger teeth and displays greater variation in occlusal structure. Based on the high frequency of cingular remnants and light to moderate enamel wrinkling of the molars, we assigned the Yicun fossils to Pongo weidenreichi, a species that was widespread in southern China throughout the Pleistocene. Lastly, we used published stable carbon isotope data of Early to Late Pleistocene mammalian fossil teeth from mainland Southeast Asia to reconstruct changes in the paleoenvironment and to interpret dental size variation of Pongo assemblages in a broader temporal and environmental context. The carbon isotope data show that dental size reduction in Pongo is associated with environmental changes. These morphological changes in Pongo appear to coincide with the expansion of savannah biomes and the contraction of forest habitats from the Middle Pleistocene onward. The variation in dental size of forest-dwelling Pongo in mainland Southeast Asia may have resulted from habitat differentiation during the Pleistocene.